Genetic analysis of heat stress tolerance in Indian mustard (Brassica juncea L.) - Bhagirath Ram; VV Singh; HS Meena; A Kumar; BK Singh; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
A set of fifty-three Indian mustard [Brassica juncea (L.) Czern & Coss.] genotypes were evaluated for geneticvariability and correlation for yield and physiological characters during rabi 2012-13 and 2013-14 under heatstress (early sown), and normal (optimum time) environmental conditions. The study was undertaken togenerate genetic information for seed yield per plant (g), population survival (%) at 10 and 25 days aftersowing (DAS), membrane stability index (%), excised-leaf water loss (%), relative water content (%), waterretention capacity of leaves (%), 1000-seed weight (g), and oil content (%), and quantification of relationshipsamong these characters. Significant differences were observed for all the characters among the genotypes,except 1000-seed weight, which revealed the presence of sufficient variability for these characters. Highestimates of PCV for MSI, seed yield per plant, and population survival (PS) 25DAS indicated the importanceof additive genes. High heritability estimates coupled with high to moderate genetic advance as per cent ofmean was recorded for PS 25DAS, WRCL, and RWC indicating the role of additive gene action for itsinheritance, and could be improved through selection. Oil content had low heritability estimates along with lowgenetic advance, indicating non-additive gene activity, and this could be improved through hybridization.Character association analysis revealed that seed yield per plant showed positive, and highly significantcorrelations with RWC (r=0.407**) which could be considered as one of the important selection criteria inthe improvement of seed yield under heat stress situation.